Benefits of non‐invasive ventilation in acute hypercapnic respiratory failure. Issue 4 (12th January 2019) - Comellini, Vittoria; Pacilli, Angela Maria Grazia; Nava, Stefano
ABSTRACT: Non‐invasive ventilation (NIV) with bilevel positive airway pressure is a non‐invasive technique, which refers to the provision of ventilatory support through the patient's upper airway using a mask or similar device. This technique is successful in correcting hypoventilation. It has become widely accepted as the standard treatment for patients with hypercapnic respiratory failure (HRF). Since the 1980s, NIV has been used in intensive care units and, after initial anecdotal reports and larger series, a number of randomized trials have been conducted. Data from these trials have shown that NIV is a valuable treatment for HRF. This review aims to explore the principal areas in which NIV can be useful, focusing particularly on patients with acute HRF (AHRF). We will update the evidence base with the goal of supporting clinical practice. We provide a practical description of the main indications for NIV in AHRF and identify the group of patients with hypercapnic failure who will benefit most from the application of NIV.